2020
DOI: 10.1136/bmjdrc-2020-001229
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime duration of lactation and chronic inflammation among middle-aged women with a history of gestational diabetes

Abstract: IntroductionLonger duration of lactation is associated with lower cardiometabolic disease risk, but pathogenic pathways involved in the disease progression are unclear, especially among high-risk women. We aimed to examine the associations of lifetime lactation duration with cardiometabolic biomarkers among middle-aged women with a history of gestational diabetes (GDM).Research design and methodsWomen with a history of GDM participating in the Nurses’ Health Study II, a prospective cohort study, were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“… 20 23 25 26 One study found a significant association between breastfeeding duration and lower CRP in middle-aged women with a history of GDM. 26 It is worthy to point out that in our cohort, breastfeeding was not associated with TNF-α or IL-6 at 1 year postpartum. Different mechanisms might be involved in the long-term and short-term regulation and expression of these inflammatory markers in the blood in women with GDM, suggesting that the impact of breastfeeding might not be the same.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“… 20 23 25 26 One study found a significant association between breastfeeding duration and lower CRP in middle-aged women with a history of GDM. 26 It is worthy to point out that in our cohort, breastfeeding was not associated with TNF-α or IL-6 at 1 year postpartum. Different mechanisms might be involved in the long-term and short-term regulation and expression of these inflammatory markers in the blood in women with GDM, suggesting that the impact of breastfeeding might not be the same.…”
Section: Discussionmentioning
confidence: 55%
“…6 Measures Breastfeeding duration served as the predictor, and we assessed metabolic, inflammatory, and bone density measures at 1 year postpartum. Sociodemographic, descriptive health, and lifestyle characteristics Sociodemographic variables including age, educational level, and ethnicity were assessed during the first GDM visit (24)(25)(26)(27)(28)(29)(30)(31)(32). Data on medical characteristics including pre-pregnancy weight, parity, gravida, GDM Clinical care/Education/Nutrition in previous pregnancy, family history of diabetes, and medical treatment were extracted from the patients' medical chart or assessed during a structured face-to-face interview.…”
Section: Gdm Management and Patient Follow-upmentioning
confidence: 99%